Pharmacy-based interventions to increase vaccine uptake: report of a multidisciplinary stakeholders meeting - Fiona Ecarnot; Gaetano Crepaldi; Philippe Juvin; John Grabenstein; Giuseppe Del Giudice; Litjen Tan; Susan O'Dwyer; Susanna Esposito; Xavier Bosch; Gaetan Gavazzi; John Papastergiou; Jacques Gaillat; et al. (BMC, 2019)
Abstract Background Despite the existence of efficacious vaccines, the burden of vaccine-preventable diseases remains high and the potential health benefits of paediatric, adolescent and adult vaccination are not being achieved due to suboptimal vaccine coverage rates. Main body of abstract Based on emerging evidence that pharmacy-based vaccine interventions are feasible and effective, the European Interdisciplinary Council for Ageing (EICA) brought together stakeholders from the medical and pharmacy professions, the pharmaceutical industry, patient/ageing organisations and health authorities to consider the potential for pharmacy-based interventions to increase vaccine uptake. We report here the proceedings of this 3-day meeting held in March 2018 in San Servolo island, Venice, Italy, focussing firstly on examples from countries that have introduced pharmacy-based vaccination programmes, and secondly, listing the barriers and solutions proposed by the discussion groups. Conclusions A range of barriers to vaccine uptake have been identified, affecting all target groups, and in various countries and healthcare settings. Ease of accessibility is a potentially modifiable determinant in vaccine uptake, and thus, improving the diversity of settings where vaccines can be provided to adults, for example by enabling community pharmacists to vaccinate, may increase the number of available opportunities for vaccination.